From skills to survival: How education mediates entrepreneurial competencies and resilience in people with disabilities - Junid , Junainah; Ngah, Rohana; Abdul Kadir , Mohamad Ali Bahri; Mat Nawi, Farahiyah Akmal (International Journal of Accounting, Finance and Business, 2025)
People with disabilities in Malaysia experience disproportionately high unemployment, driven by societal bias, inaccessible infrastructure, and skill mismatches. Entrepreneurship offers a viable pathway to economic independence, yet success requires more than access to opportunity. It hinges on entrepreneurial competencies such as proactiveness, risk-taking, opportunity recognition, and innovativeness. This study investigates how these competencies foster entrepreneurial resilience, focusing particularly on the mediating role of education. A total of 379 Malaysians with physical disabilities were surveyed through face-to-face and online methods. Using Partial Least Squares Structural Equation Modelling (PLS-SEM), the analysis revealed that higher levels of these competencies significantly enhance entrepreneurial resilience, especially when supported by educational attainment. While education’s mediating role was less dominant than direct competency effects, it amplified key competencies like proactiveness and opportunity recognition. PWDs with formal education were notably more capable of diversifying income sources during crises. The study advocates for inclusive policy interventions that integrate competency-based entrepreneurship education, digital accessibility, and community-based mentorship to reduce structural barriers and promote sustainable livelihoods for PWDs.